1987
DOI: 10.1002/chin.198737311
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Synthesis and Pharmacological Evaluation of γ‐Aminobutyric Acid Analogues. New Ligand for GABAB Sites.

Abstract: Reaction of the phenol (I) with the chlorides (II) and subsequent basic ring cleavage yield the amino acids (III).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…Previous results obtained with the 4-hydroxybaclofen analogue showed it was completely inactive in binding GABAb tests. 14 In the present paper, our results suggest also that the substituent in the para position on the aromatic or pseudoaromatic ring should be of lipophilic nature to observe high affinity. The higher activity of thienyl analogues (5c » 5a and 5d » 5b) could be explained by the higher electronegativity of the oxygen atom in comparison with that of the sulfur atom.…”
Section: Discussionsupporting
confidence: 64%
“…Previous results obtained with the 4-hydroxybaclofen analogue showed it was completely inactive in binding GABAb tests. 14 In the present paper, our results suggest also that the substituent in the para position on the aromatic or pseudoaromatic ring should be of lipophilic nature to observe high affinity. The higher activity of thienyl analogues (5c » 5a and 5d » 5b) could be explained by the higher electronegativity of the oxygen atom in comparison with that of the sulfur atom.…”
Section: Discussionsupporting
confidence: 64%
“…From the structural analysis of diverse GABA B receptor agonists, we determined that the substitution of the chlorine atom in the para position of the aromatic ring by electron donating groups (R = i ‐Pr, CH 2 C 6 H 5 , CH 2 ‐4‐F‐C 6 H 4 , and CH 2 ‐5‐Cl‐thienyl) generate inactive compounds of general structure 25 (Figure ) (Berthelot et al., ). Substitution of the aromatic ring by benzofuran type groups produced two analogues, 26 and 27 , which in [ 3 H] Baclofen binding assays were active at concentrations of IC 50 = 18 μM and IC 50 = 5.6 μM, respectively (Berthelot et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…These molecules possess the Baclofen pharmacophoric groups and their biological activity was determined in different biological systems. (Attia et al., ; Berthelot et al., , ; Man et al., ).…”
Section: Computational Detailsmentioning
confidence: 99%
“…Initial attempts yielded phosphonic and sulfonic acid analogues of baclofen as well as 3-benzo [b] furan-2-yl-GABA derivatives, all of which have relatively low affinities for the receptor and are ineffective following systemic administration [29][30][31][32]. Structure-activity studies with phosphinic GABA B receptor agonists revealed that ethylphosphinic acid, and higher homologues, are receptor antagonists (Figure 2; [16]).…”
Section: Gabab Receptor Antagonistsmentioning
confidence: 99%